Pemberdayaan Ibu-Ibu melalui Pelatihan Pembuatan Sabun Cuci Piring Ramah Lingkungan - Nuragustin Nuragustin; Rafli Aditya Ramadhan S; Hanif Abrar; Friyadi Hamonangan; Yahfizham Yahfizham (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
This Community Service Program (KKN) was implemented as an effort to address the health and environmental risks associated with the use of chemical-based dishwashing soap. The program’s lack of knowledge and skills in making natural household products among women underpins the program’s implementation. The goal was to raise awareness and empower women through training in making environmentally friendly dishwashing soap. The program was conducted at the Women’s Witness Building and included outreach, demonstrations, hands-on practice, discussions, and the sharing of results. During the workshop, participants were taught how to make soap using simple ingredients such as baking soda, liquid soap, water, and the addition of glycerin, dyes, and fragrances. The results demonstrated high enthusiasm from the participants, reflected in their active involvement during the workshop and their understanding of the benefits of natural products. This activity not only improved the women’s skills but also encouraged a frugal, healthy, and environmentally conscious lifestyle.